2017
DOI: 10.1155/2017/9402386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marathon Running on Aerobic Fitness and Performance in Recreational Runners One Week after a Race

Abstract: It is not clear whether or not recreational runners can recover aerobic fitness and performance within one week after marathon running. This study aimed to investigate the effects of running a marathon race on aerobic fitness and performance one week later. Eleven recreational runners (six men, five women) completed the race in 3 h 36 min 20 s ± 41 min 34 s (mean ± standard deviation). Before and 7 days after the race, they performed a treadmill running test. Perceived muscle soreness was assessed before the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…Previous studies demonstrated that hematological and biochemical markers changed immediately following the sport and returned to baseline levels after 2-7 days of recovery in the amateur half-marathon runners [1]. Several hormonal markers, such as insulin, leptin and adiponectin, showed unique patterns after a marathon running [9].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies demonstrated that hematological and biochemical markers changed immediately following the sport and returned to baseline levels after 2-7 days of recovery in the amateur half-marathon runners [1]. Several hormonal markers, such as insulin, leptin and adiponectin, showed unique patterns after a marathon running [9].…”
Section: Introductionmentioning
confidence: 95%
“…In order to achieve excellent performance, runners make efforts in exercise training. Usually, after runners complete a full marathon match, their skeletal muscle, myocardium, liver, and other tissues are presented with an elevated free radical production, lipid peroxidation and disordered ion and energy metabolism, which lead to exercise-induced fatigue [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a time lag existed between treadmill running test and recent marathon race in the present study (n=35, 154±111 days), suggesting that the classic physiological variables may change somewhat from those in the race. Takayama et al (2017) showed that approximately 80z of recent marathon time could be explained using vAT (r=0.897, p< 0.001) in 11 recreational runners who completed the same race one week before the test. Compared with that previous report, the explanatory rate in this study was relatively lower (67z).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RER1.0 is a useful method for measuring distance performance in recreational runners. A recent study has indicated that there were signiˆcant relationships between vAT, which was quantiˆed by the RER1.0 method, and recent marathon time in 11 recreational runners who completed the same race one week before the test (Takayama et al, 2017). In that study, however, the sample size was relatively small and the detailed relationship between classic physiological variables and performance was not reported (Takayama et al, 2017).…”
Section: Introductionmentioning
confidence: 94%